American politics today - William T. Bianco (Norton, 2009)
There is a common belief among college students that American politics and government are broken, or too complicated to understand, or completely illogical. With a student-friendly analytical framework and vivid, current examples, American Politics Today demystifies the political process and shows students how the system actually workseffectively and powerfully